Silver N-Heterocyclic Carbene (NHC) Complexes as Antimicrobial and/or Anticancer Agents - Jessica Ceramella; Alessia Catalano; Annaluisa Mariconda; Assunta D’Amato; Saveria Aquila; Carmela Saturnino; Camillo Rosano; Maria Stefania Sinicropi; Pasquale Longo (Pharmaceuticals)
The strict connections/interactions between microbial infections and cancer are nowadays widely accepted. Hence, the dual (or multiple) targeting of microbial infections and cancer is an essential issue to be addressed. In this context, metal complexes have gained considerable importance and effectiveness in medicinal chemistry. Particularly, N-heterocyclic carbene (NHC) complexes with transition metals have emerged as very promising compounds. Among the myriad of NHC–metal complexes, those bearing silver will be the subject of this review. Numerous Ag(I)-NHC complexes have revealed high antibacterial and/or anticancer properties, even higher than those of reference drugs. Herein, we summarize the most recent studies while also discussing the proposed mechanism of action and offering an interesting remark about the research in this field. Literature databases (PubMed/MEDLINE, Scopus, and Google Scholar) were used as sources to search the literature, referring to the last five years.